(untitled) (Dhaka Shishu (Children) Hospital Journal, 2021)
Background: Infantile haemangiomas (IH) are the most common tumors ofinfancy with an incidence of >2% of infants in general, and of 10% of Caucasian children, in particular. Objective: The aim of this study was to assess the efficacy and safety of atenolol in the treatment of proliferating IHs. Methods: This prospective study was conducted among 120 patients’ up to 30 months of age, clinically diagnosed with IH’s in surgical outpatient department (SOPD) of the Dhaka Shishu Hospital from July 2013 to March 2018. Atenolol was started initially 0.5mg/kg. Then doses were titrated according to clinical response (0.5- 3mg/kg/day OD). Parents were instructed to interrupt the administration of the drug if the child had a serious cough with dysponea or gastroenteritis with vomiting or diarrhoea. Patients’ were advised to come for follow up visit and in each follow up blood pressure, percentage of regression (of size), color change, complications were recorded. The change in the appearance of IH was evaluated on a visual analogue scale (VAS). Regression in the size and color clearance of IHs were evaluated according to 0%-to-100% scale. Results: Majority of the babies were from 1-10 months age group. Most of the infants were term babies and majority of the infants were girls. Majority of the IHs were located in head and neck regions. Majority of the mothers had multiple gestation pregnancy and few had family history of IH. Excellent, good and fair colour regression was found in 74.17%, 22.50% and 3.33% participants respectively. Excellent, good and fair size regression was found in 57.50%, 38.33% and 4.17% participants respectively. Adverse effects of drug like loose motion (7.50%) and sleep disturbance (3.33%) were found among the participants. DS (Child) H J 2018; 34(1) : 26-29